Orphans of the storm ebook - Imrie, Celia (2021)
From internationally bestselling author and celebrated actress Celia Imrie, an epic novel set against the backdrop of the sinking of the Titanic . Nice, France, 1911: After three years of marriage, Marcella Navratil has finally had enough. Her husband, Michael, an ambitious tailor, may have charmed her during their courtship, but their few years of marriage have revealed a cruel and controlling streak. The 21-year-old mother of two is determined to get a divorce. But while awaiting the Judges' decision on the custody of their children, Michael receives news that changes everything. Meanwhile fun-loving New York socialite Margaret Hays is touring Europe with some friends. Restless, she resolves to head home aboard the most celebrated steamer in the world. But as the ship sets sail for America, carrying two infants bearing false names, the paths of Marcella, Michael and Margaret cross and nothing will ever be the same again. Orphans of the Storm dives into the waters of the past to unearth a sweeping, epic tale of the sinking of the Titanic that radiates with humanity and hums with life.